Induction and identification of polyploids in Cattleya intermedia Lindl. (orchidaceae) by in vitro techniques Indução e identificação de poliploides em Cattleya intermedia Lindl. (orchidaceae) através de técnicas in vitro - Paulo Artur Konzen Xavier de Mello e Silva; Sídia Callegari-Jacques; Maria Helena Bodanese-Zanettini (Ciência Rural, 2000)
The effect of colchicine on the protocorm-like bodies of Cattleya intermedia L. (Orchidaceae) cultured in vitro was studied. Different concentrations of the drug (0.00, 0.05, 0.10 and 0.20%) as well as two times of culture (4 or 8 days) were tested to determine the best treatment for the induction of tetraploid plants. Of the 3 colchicine levels applied, 0.05 and 0.10% of drug treatments appeared to be effective on the production of mixoploids and tetraploids and could be further used in breeding programs. The suitability of stomatal area and stomata density as criteria for the distinction between diploids and tetraploids was also tested. The results suggested that tetraploid plants could be identified with a fair amount of certainty when the screening was based on the density of stomata. No presente trabalho, foi estudado o efeito da colchicina em corpos semelhantes a protocormos de Cattleya intermedia L. (Orchidaceae). Diferentes concentrações da droga (0,00; 0,05; 0,10 e 0,20%), bem como diferentes tempos de cultura (4 ou 8 dias) foram testados para determinar o melhor tratamento para a indução de plantas tetraplóides. Dos três níveis de colchicina aplicados, os tratamentos com 0,05 e 0,10% da droga parecem ser mais efetivos na produção de mixoplóides e tetraplóides, sendo que tais tratamentos podem ser utilizados em programas de melhoramento. Como critério para distinção entre diplóides e tetraplóides, foram realizadas medidas de área de estômatos e densidade de estômatos das folhas. Os resultados sugerem que as plantas tetraplóides podem ser identificadas com elevado grau de certeza quando a seleção é realizada com base na densidade de estômatos.